An Introduction to Waste Management and Circular Economy - van Ewijk, Stijn; Stegemann, Julia (Open textbook library., 2023)
This introductory textbook provides an essential interdisciplinary guide to waste management and circular economy. It helps students to understand the drivers of waste, the environmental, social, and economic impacts of waste generation, and best practices and technologies for waste management, recycling, energy recovery and disposal. With helpful, full-colour diagrams throughout, each chapter includes learning objectives, introduction to concepts and themes, exercises and review sections, to guide students through the book. The textbook is ideal for teaching environmental engineering and science, as well as interdisciplinary environmental programmes.